Scientific publication: policy on open access (European Research Advisory Board Final Report) - Grimson, Jane; European Research Advisory Board; Brennan, Niamh (EURAB, 2006)
EURAB was invited by the Commission to examine the issue of scientific publication with particular reference to policy recommendations regarding open access for Framework Programme 7 (FP7). A clear policy at European level is required which sets out a number of key high level principles. The forthcoming Communication on scientific information scheduled for publication in late 2006 or early 2007 will be a key milestone in this respect. The Commission can play a role in three respects: as a funding body, as a policy body, as a supporting body. These roles are outlined and an open access publications mandate is proposed for the European Commission.
Keywords: Open Access; Scholarly publications; European policy; Digital Engagement; Inclusive Society